RADEC Learning Model with the Assistance of Media Question Box to Improve Primary School Students' Critical Thinking Ability - Candraswari, Ni Komang Triana; Suniasih, Ni Wayan (Thinking Skills and Creativity Journal, 2024)
Students' critical thinking abilities in the science and science learning process are still low and need to be improved. Therefore, there is a need for a learning model that can improve students' critical thinking abilities. The RADEC learning model combined with Question Box media is a solution to this problem. This research aims to analyze the effect of the RADEC learning model assisted by Question Box media on the critical thinking abilities of fourth grade students in science and science lessons. This research uses a quasi-experimental research design with a non-equivalent control group research design. The population of this study was all 418 grade IV students. The sampling technique chosen was cluster random sampling which obtained 28 students as the experimental class and 28 students as the control class. The data collection method uses tests in the form of descriptions. Critical thinking ability data obtained from the post-test results were analyzed using descriptive statistical techniques and inferential statistical analysis using the polled variance t-test. Based on the research conducted, it was concluded that the RADEC learning model assisted by Question Box media had an effect on the critical thinking skills in science and science lessons for fourth grade elementary school students.